PENURUNAN MODEL PERMUKAAN DIJITAL (DSM) MENJADI MODEL ELEVASI DIJITAL (DEM) DARI CITRA SATELIT ALOS PALSAR (Studi kasus: NAD Bagian Tenggara, Indonesia) - Julzarika, Atriyon; Sudarsono, Bambang (TEKNIK, 2009)
Alos satellite is one of the natural resources satellite that could be used in 3D applications. The problemsthat be taken in generate 3D model with satellite imagery are the model always be formed as DigitalSurface Model (DSM), not Digital Terrain Model (DTM), Digitallen HÃ¶heModellen (DHM), Digital GeoidModel (DGM) or Digital Elevation Model (DEM). The reference system of 3D model that are produced byAlos satellite image still as surface for z axis, for x axis and y axis has been closed to 2D reference systemin some certain datum and system of map projection. In case, it needs a research for observating theaccuracy and precision of Alos satellite data using a least square adjustment of parameter methods. Theresults of this research will be used as reference for next research to invent a way for changing DSM fromAlos satellite image to be DEM, DTM, DHM, DHM, and DGM digital-automatically. It is a new innovationof differentialing technical of 3D model.A differentialing technical from DSM to be DEM could be done with least square adjustment in parametermethods. It calls DSM2DEM*. This new innovation methods for differentialing DSM2DEM. In that studycases, differentialing technical that are used be divided for two class, that are lowland area and highlandarea. Differentialing in that two class use similar methods, just is differentiated in sum up of researchingpoints that are used. In this research study of cases are in highland area and lowland area. In highlandarea uses minimize 14 researching points and in lowland area uses minimize seven researching points.That differentialing technical are done in Alos images. In other satellite images, photos, videos that studyin highland and lowland area also use this methods for differentialing DSM2DEM. Order level that areused as research points will influence the quality of its data accuracy and precision.